Satisfaction of Tourist at the Tourist Destination Portorož - Piran (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
In our research we measured tourist satisfaction at the destination Portorož - Piran. The survey was conducted with the continuous monitoring methodology, according to the criteria given by the Directorate for Tourism of Slovenia, along with their standardized questionnaire for tourist destinations, which is based on the world-renowned models of user satisfaction. We administered the questionnaires in the period of high season, during summer from June till September and in December 2013. Several factors were analysed: the socio-demographic structure of the tourists, their countries of origin, their main tourist motives for visiting this tourist destination, their sources of information about the resort, the frequency and length of the tourists' stay, their placement according to individual accommodation facilities, the tourists' therapeutic, sport, recreational and other needs, their satisfaction with health care and tourists' provisions, planned trips at the tourist destination and its surroundings. The goal of this paper is to determine the level of satisfaction of tourists at the tourist destination Portorož - Piran in the high season. In addition, we examined the theoretical knowledge, of renowned domestic and foreign experts, on the satisfaction of tourist and related factors, determined the level of tourist satisfaction and factors that influence the satisfaction of tourists in this destination, we identified the main tourist motives (desires and expectations), identified possible shortcomings in this tourist destination and developed recommendations for professionals.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.